The performance of the real estate listed on the stock exchange in the context of management with business agents - เฟื่องวงศ์ นงนุช; Piriyakul, Rapeepun (Business Administration and Management Journal Review, 2020)
According to be an executive as the business agent, there are many suspected issues such as the capacity in selecting the strategy and policy deployment. In addition, the moral and ethics in acting as the shareholder’s agent are the awareness factors on the shareholder. To study the performance of the real estate listed on the stock exchange in the context of management by business agent, we explored the relevance features from previous work. The determinant features on business performance (which conduct from factor analysis on profit, asset, and debt) are the business strategy, CEO shareholder, executives, female executives, and registered capital. However, we confirm the hypothesis based on three Mathematical techniques, and the results have shown that the female executive was not significant, the different of CEO shareholder in period t and t-1 has the negative effect while the other variables have the positive effects on the business performance. The investigation was conducted on 40 firms form the Thai real estate listed on the stock exchange (10 years from 2550 to 2559).